دور الخط العربي في تصميم الإعلان المطبوع - يونس, نورا (Latakia University Journal -Engineering Sciences Series, 2018)
This research explains the Role of Arabic Calligraphy in the Design of Printed Advertisements. In recent decades, Arabic calligraphy has seen its fair share of development and growth, brought upon by the increased technological advancement, which paved the way for it to enter the world of digital printing and take on new shapes and forms, some artistic, others functional. These changes were the inspiration behind a new wave of authentic and pioneering visual content which focuses on the artistic aspects of Arabic calligraphy and highlights its aesthetic role in graphic design, modern printouts and other written and visual mediums. يتمحور هذا البحث حول دور الخط العربي في تصميم الإعلان المطبوع، فالخط العربي الآن لم ينفصل عن التطور الذي شهدته مناحي الحياة عامة وخاصة التكنولوجية منها، حيث استطاع الخط العربي الدخول لعالم الطباعة الرقمية بأشكالها المختلفة وذلك بظهوره بأشكال متعددة منها الفني ومنها الوظيفي، وهكذا ولد تيار استلهام الخط العربي في تحقيق منجز بصري حروفي معاصر، يتمتع بالأصالة والتفرد مركزاً على الجوانب الفنية والتشكيلية له، بهدف معرفة ما يمكن أن يدعم الدور الجمالي والمعنوي لهذا الخط كعنصر من عناصر التصميم الغرافيكي والمطبوعات المعاصرة، كوسائل اتصال مكتوبة ومرئية.